Electrodeposited carbonyl functional polymers as suitable supports for preparation of the first-generation biosensors - Sýs, Milan; Bártová, Michaela; Mikysek, Tomáš; Švancara, Ivan (My University, 2023)
The aim of this electrochemical study was to ascertain which type of electrochemically deposited carbonyl functionalized polymer represents the most suitable electrode substrate for direct covalent immobilization of biological catalysts (enzymes). For this purpose, a triad of amperometric biosensors differing in the type of conductive polymers (poly-vanillin, poly-trans-cinnamaldehyde, and poly-4-hydroxybenzaldehyde) and in the functioning of selected enzymes (tyrosinase and alkaline phosphatase) has been compared for the biosensing of neurotransmitters (dopamine, epinephrine, norepinephrine, and serotonin) and phenyl phosphates (p-aminophenyl phosphate and hydroquinone diphosphate). The individual layers of the polymers were electrochemically deposited onto commercially available screen-printed carbon electrodes (type C110) using repetitive potential cycling in the linear voltammetric mode. Their characterization was subsequently performed by SEM imaging and attenuated total reflectance FTIR spectroscopy. Molecules of enzymes were covalently bonded to the free carbonyl groups in polymers via the Schiff base formation, in some cases even with the use of special cross-linkers. The as-prepared biosensors have been examined using cyclic voltammetry and amperometric detection. In this way, the role of the carbonyl groups embedded in the polymeric structure was defined with respect to the efficiency of binding enzymes, and consequently, via the final (electro)analytical performance.
Elektrolyticky deponované polymery s karbonylovou funkční skupinou jako vhodné nosiče pro přípravu biosenzorů první generace
Keywords: Amperometric detection; carbonyl functional polymer; catalytic biosensor; electropolymerization; enzyme; phenolic compounds; Schiff-base formation; Amperometrická detekce; polymer s karbonylovou funkční skupinou; katalytický biosenzor; elektropolymerizace; enzym; fenolové sloučeniny; tvorba Schiffových bází